“We Need to be Better”: Race, Outdoor Recreation, and Corporate Social Advocacy - Tarin, Carlos Anthony; Upton, Sarah De Los Santos; Hernández, Leandra Hinojosa (Frontiers in Communication, 2021)
The summer 2020 protests following the killings of George Floyd, Breonna Taylor, Ahmaud Arbery, and other African-Americans sparked important conversations about race, police brutality, and institutionalized racism in the United States. In response to widespread civil unrest, organizations across the country issued statements condemning anti-Black violence and supporting the Black Lives Matter movement. This essay analyzes public statements released by 50 outdoor sport and recreation organizations. Extending scholarly literature on race and corporate social advocacy, our analysis develops the concept of conciliatory discourse, which functions by rhetorically constructing 1) a non-specification of grievance, 2) an obfuscation of commitments to action, and 3) a reinforcement of previous actions or processes. We argue that while many outdoor recreation organizations took action in support of racial justice, their public statements complicate long-term commitments for inclusivity and diversity.